In vivo assessment of muscle membrane properties in myotonic dystrophy. Issue 2 (24th May 2016) - Tan, S. Veronica; Z'graggen, Werner J.; Boërio, Delphine; Turner, Christopher; Hanna, Michael G.; Bostock, Hugh
ABSTRACT: Introduction : Myotonia in myotonic dystrophy types 1 (DM1) and 2 (DM2) is generally attributed to reduced chloride‐channel conductance. We used muscle velocity recovery cycles (MVRCs) to investigate muscle membrane properties in DM1 and DM2, using comparisons with myotonia congenita (MC). Methods : MVRCs and responses to repetitive stimulation were compared between patients with DM1 ( n = 18), DM2 ( n = 5), MC ( n = 18), and normal controls ( n = 20). Results : Both DM1 and DM2 showed enhanced late supernormality after multiple conditioning stimuli, indicating delayed repolarization as in MC. Contrary to MC, however, DM1 showed reduced early supernormality after multiple conditioning stimuli, and weak DM1 patients also showed abnormally slow latency recovery after repetitive stimulation. Conclusions : These findings support the presence of impaired chloride conductance in both DM1 and DM2. The early supernormality changes indicate that sodium currents were reduced in DM1, whereas the weakness‐associated slow recovery after repetitive stimulation may provide an indication of reduced Na + /K + ‐ATPase activation. Muscle Nerve 54 : 249–257, 2016